Raden Saleh dan Restorasi Makam Tahun 1953: Penghormatan Pelukis Bumiputera dan Penguatan Identitas Nasional pada Masa Kekuasaan Soekarno - Siti Amalia; Syarif Hidayatullah; Masthuroh Zakiyah; Faizal Arifin - (UIN Sunan Gunung Djati Bandung, 2023)
Raden Saleh, the first painter in Java to adopt modern techniques and gain recognition in the Western world during the Dutch colonial era, holds an important place in Indonesian art history. This article examines the life and contributions of Raden Saleh. It explores the restoration of his tomb by President Soekarno as a means to strengthen Indonesia's national identity in the post-independence period. The research utilizes historical methods, including heuristics, source criticism, interpretation, and historiography. The study reveals that the restoration of Raden Saleh's tomb in 1953, under President Soekarno's leadership, aimed to pay homage to Raden Saleh as a prominent figure in Indonesian history and reinforce the Indonesian identity by recognizing the globally renowned indigenous elite. Although Raden Saleh passed away long before Indonesia's independence, and the concept of Indonesia as a nation emerged much later, the government, particularly under President Soekarno and Minister of Education and Culture Mohammad Yamin, believed that the restoration was necessary due to the unsatisfactory condition of the tomb. Additionally, the presence of paintings reflecting indigenous perspectives and occasionally criticizing colonialism influenced the decision to restore the tomb. This research sheds light on the significance of Raden Saleh's legacy in shaping Indonesian art and the efforts to preserve cultural heritage in the nation. Keywords: Culture, Raden Saleh, Restoration, Soekarno